Students’ Pedagogic and Professional Competencies in Teaching Practice Program - HB, Zulfahmi; Trinova, Zulvia; Mahmud, Mahmud (AT-TA'LIM, 2020)
The research aims to describe pedagogical and professional competencies of students who enroll at the department of Islamic elementary education at Faculty of Tarbiyah and Teacher Training UIN Imam Bonjol Padang. A mixed method was implemented where the data collected through observation, interviews, questionnaires, and documentation. The results of the study on aspects of pedagogical competence was at the level of very good (82.4%). It was also found that the criteria to master the characteristics of students from the physical, moral, spiritual, social, cultural, emotional, and intellectual aspects were very good (80%), carrying out educational learning was very good (81%), facilitating the development of potential students to actualize various potentials which was very good (83%), communicating effectively, empathically, and politely with 88% of students (very good), and in evaluating and evaluating 80% (very good). While professional competence was with a value of 78.3% (good). Among the mastery of teaching material 78.5% (good), the use of learning media 77.5% (good), as well as contextual material or connecting teaching materials with the daily life of students 79% (good). The study recommended that prospective educators further improve pedagogical and professional competencies, often take part in training activities, practice teaching simulations. For the department of Islamic elementary education should be more professional to guide students during teaching practice programme activities, and lectures, especially in the field of teacher competency development.